Analisis Keuntungan Usahatani Tomat Beef Hidroponik di Desa Cibodas, Kecamatan Lembang, Kabupaten Bandung Barat - Br Ginting, Novia Maharani; Rochdiani, Dini (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Beef tomatoes have good market prospects because they are attractive in appearance and meet the needs of the fresh market, resulting in high sales and relatively stable demand. Beef tomatoes can be cultivated using a hydroponic system in a greenhouse. This system can improve quality and productivity, but requires a relatively large allocation of funds to run production activities, making it an important factor affecting the structure and level of agricultural profits. This study aims to analyze the profitability of beef tomato farming using the hydroponic system in Cibodas Village, Lembang Subdistrict, West Bandung Regency. The study employs a survey method. The research location was deliberately chosen because farmers in Cibodas Village actively engage in hydroponic beef tomato cultivation. The results of the study indicate that hydroponic beef tomato farming in Cibodas Village requires an average cost of Rp23,251,347.92 and generates an average income of Rp40,416,250.00, resulting in an average profit of Rp17,164,902.08 per growing season with an RC ratio of 1.74, indicating that this business is viable and provides good returns.